2014
DOI: 10.1371/journal.pone.0112068
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem Reduces Hippocampal Neuronal Activity in Freely Behaving Mice: A Large Scale Calcium Imaging Study with Miniaturized Fluorescence Microscope

Abstract: Therapeutic drugs for cognitive and psychiatric disorders are often characterized by their molecular mechanism of action. Here we demonstrate a new approach to elucidate drug action on large-scale neuronal activity by tracking somatic calcium dynamics in hundreds of CA1 hippocampal neurons of pharmacologically manipulated behaving mice. We used an adeno-associated viral vector to express the calcium sensor GCaMP3 in CA1 pyramidal cells under control of the CaMKII promoter and a miniaturized microscope to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…Wireless electrophysiological recordings from multiple animals in parallel are already widely used in behavioral neuropharmacology studies, and a wireless approach to cellular imaging might notably benefit pre-clinical and therapeutic discovery efforts. To date, brain imaging in freely moving mice has been combined with wireless telemetry systems that transmit electroencephalography (EEG) and electromyography (EMG) signals (Berdyyeva et al, 2014). There have also been efforts to improve the throughput of imaging studies in head-restrained rats, by allowing rats to initiate brief periods of voluntary head restraint underneath the objective lens of a conventional two-photon microscope (Scott et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wireless electrophysiological recordings from multiple animals in parallel are already widely used in behavioral neuropharmacology studies, and a wireless approach to cellular imaging might notably benefit pre-clinical and therapeutic discovery efforts. To date, brain imaging in freely moving mice has been combined with wireless telemetry systems that transmit electroencephalography (EEG) and electromyography (EMG) signals (Berdyyeva et al, 2014). There have also been efforts to improve the throughput of imaging studies in head-restrained rats, by allowing rats to initiate brief periods of voluntary head restraint underneath the objective lens of a conventional two-photon microscope (Scott et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the illumination and fluorescence image propagated to and from the mouse via a fiber-optic bundle (Flusberg et al, 2008; Murayama and Larkum, 2009; Murayama et al, 2007, 2009; Soden et al, 2013), but the subsequent approach of integrating all optical components within the head-mounted device has proven notably superior regarding the optical sensitivity, field of view, resolution, mechanical flexibility for the animal, and portability between experimental sites that can be attained (Ghosh et al, 2011). Using a fingertip-sized integrated microscope (Figure 4A) that combines a blue light-emitting diode (LED), a cell phone CMOS camera chip for digital imaging, miniaturized lenses, and a fluorescence filter set within a single compact housing, one-photon imaging of neural Ca 2+ signals in freely behaving mice has become more widespread since the initial experiments (Figures 4B–4F) (Berdyyeva et al, 2014; Ghosh et al, 2011; Jennings et al, 2015; Ziv et al, 2013). The integrated microscope has a ~0.5 mm 2 field of view (Ghosh et al, 2011), which permits dense sampling of up to ~1,000 individual neurons simultaneously (Alivisatos et al, 2013; Chen et al, 2013a; Ziv et al, 2013), about 20–50 times more cells than can be individually monitored in behaving mice using electrophysiological methods.…”
Section: Optical Imaging Paradigms For Studies In Behaving Animalsmentioning
confidence: 99%
“…Moreover, because in vivo electrophysiology relies on waveform shapes to differentiate individual cells from each other, it can be challenging to detect cells with sparse firing patterns or that are located within densely populated networks. Finally, the number of cells that can be detected with in vivo electrophysiology methods is often far less than the number of cells that can be monitored with the optical imaging methods described in this protocol 29,42 . Taken together, these limitations in cell identification and statistical power pose a significant disadvantage for studies that require chronic monitoring of neural activity.…”
Section: Comparison With Other In Vivo Recording Methodsmentioning
confidence: 99%
“…A recent study provided the first proof-of-principle for this approach. It showed that a systemic administration of Zolpidem, a commonly prescribed in the US GABA-A agonist drug for treating insomnia, reduces hippocampal neuronal activity in freely behaving mice [61]. While such a result may not be surprising, it suggests that comparing neuronal dynamics of drug-treated and control mice in brain disease models may help identify the effects of different molecular factors on network dysfunction and cognitive/behavioral impairments.…”
Section: Integrated Microscopy Dissemination Across Neuroscience Fieldsmentioning
confidence: 99%